Effect of Shaoyao Gancao Decoction on Inflammatory Injury of Posterior Cervical Muscle Based on miR-146a Regulation of NF-κB Signaling Pathway - Jincheng CHEN; Rong LIN; Yuanfang ZHANG; Jiquan DONG; Weilin LIU; Zheng JIANG; Shaoqing CHEN; Xiangbin WANG; Jian HE (康复学报)
Objective:To investigate the effect of Shaoyao Gancao decoction on the injury of rabbit cervical posterior myoinflammation and its possible mechanism from histology and molecular level, and provided experimental basis for the clinical application of Shaoyao Gancao decoction in the treatment of cervical spondylopathy.Methods:A total of thirty 6-month-old New Zealand white rabbits were randomly divided into high dose group, medium dose group, low dose group, model group and normal group, with 6 rabbits in each group. The model was constructed according to the cold and wet rabbit cervical spondylopathy model prepared by the research group. Eight weeks after modeling, high-dose, medium-dose, and low-dose groups were given 16,8,4 g/kg Shaoyao Gancao decoction, and the normal and model groups were fed normally. The levels of IL-1β, IL-6 and TNF-α in serum were detected by ELISA after 4 weeks of treatment. The changes of cervical muscle morphology were observed by HE staining. Western blot was used to detect the expression of myeloid differentiation factor 88 (MyD88) and nuclear factor (NF) -κB P65 protein in the key nodes of rabbit posterior cervical muscle tissue. The expression levels of miR-146a, TLR4 and TRAF-6 in posterior cervical muscle of rabbits were detected by RT-qPCR.Results:Shaoyao Gancao decoction could reduce the contents of serum inflammatory factors IL-1β, IL-6 and TNF-α in rabbits (P<0.01). It can obviously improve the morphology and structure of the muscle cells of the rabbit posterior neck damaged by inflammation. The expression levels of MyD88, NF-κB P65 were decreased (P<0.05). At the same time, the expression level of miR-146a in cervical posterior muscle tissue was increased (P<0.05), and the expression levels of TLR4 and TRAF-6 were decreased (P<0.05).Conclusion:Shaoyao Gancao decoction can reduce the inflammation and injury of the posterior cervical muscle in rabbits. The mechanism may be that by changing the expression of miR-146a in the posterior cervical muscle tissue of rabbits with cervical spondylosis, it inhibits the release of TNF-α, IL-1β, IL-6 and other inflammatory factors in the NF-κB signaling pathway, so as to improve the inflammatory injury of the neck and treat neck type of cervical spondylosis.